The effect of self-esteem, attitude towards the body, and eating habit on cognitive reactivity - Kaloeti, Dian Veronika Sakti; Ardhiani, Lusi Nur (Psikohumaniora: Jurnal Penelitian Psikologi, 2020)
An increase in the prevalence of unhealthy lifestyles, including dietary problems, is being experienced by students, especially women. This study aims to examine the model of whether self-esteem, attitude towards the body, eating habits, and Body Mass Index (BMI) affects cognitive reactivity in female students. The non-probability convenience sampling technique was employed. A total of 140 female students in Semarang, Indonesia, aged 18-22 participated in this study. The measuring instruments used were the Rosenberg Self-Esteem Scale (RSES), the Dresden Body Image Questionnaire (DBIQ), and the Adult Eating Habit Questionnaire (AEHQ). Analysis was made using partial least squares structural equation modeling (PLS-SEM). The results show that self-esteem significantly and positively affected attitudes towards the body (R2=36.3%, p<.01), and significantly and negatively affected BMI (R2=1.7%, p<.05) and cognitive reactivity (R2=35.8%, p<.01).  Furthermore, attitudes towards the body significantly mediated the relationship between self-esteem and eating habits (β = 0.166, p<.01), and also significantly mediated the relationship between self-esteem and BMI (β = -0.157, p<.01). Based on the results, the development of psychological interventions regarding self-esteem as health promotion in relation to lifestyle is highly recommended.